Development and evaluation of physical properties of a low-cost handheld device for airway clearance therapy - Cibele Cristine Berto Marques da Silva; Alba Rebeca Nery Comin; Paulo Hilario Nascimento Saldiva; Milton de Arruda de Martins; Celso Ricardo Fernandes de Carvalho (Universidade de São Paulo, 2019)
ABSTRACT Several respiratory diseases are characterized by hypersecretion, requiring airway clearance therapy (ACT). Oral high-frequency oscillation (OHFO) devices are effective to enable daily ACT; however, they are still too expensive to become available for low-income patients. We sought to develop a low-cost device (OHFO-LC) and compare its physical properties with those OHFO commercially available (Shaker and Flutter). The OHFO-LC was developed from polyvinyl chloride material and one stainless steel sphere. Pressures and frequencies were measured at flows of 4, 6, 8, 10 and 15L/min. Pressures at the mouthpieces were measured by a transducer connected to a microcomputer. The oscillation frequencies were obtained from the graph of the pressure. The frequencies and pressures were compared among groups using one-way Anova and Tukey's post hoc tests, p≤0.05. There were no differences among the frequencies of the three devices in all tested flows. The OHFO-LC device showed a higher positive expiratory pressure compared with the Shaker at all tested flows (4 L/min: 4.7±1.2 vs. 1.0±0.2 cmH2O; 6 L/min: 8.6±1.5 vs. 3.5±0.5 cmH2O; 8 L/min: 10.8±1.6 vs. 5.4±0.2 cmH2O; 10 L/min: 13.5±1.2 vs. 7.7±0.4 cmH2O; 15 L/min: 14.3±1.1 vs. 7.8±0.2 cmH2O; OHFO-LC vs. Shaker; p≤0.05) and at 10 and 15 L/min compared with Flutter (10 L/min: 13.5±1.2 vs. 7.5±1.2 cmH2O; 15 L/min: 14.3±1.1 vs. 8.2±1.2 cmH2O; OHFO-LC vs. Flutter, p≤0.05). The cost of the OHFO-LC device was much lower than both the Shaker and the Flutter. Our results showed that the OHFO-LC had physical properties with similar frequencies but higher pressures than other OHFO devices that are commercially available. Future studies are necessary to evaluate its clinical efficacy.